2022
DOI: 10.1002/adma.202108476
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Immunosuppressive Exosomes that Inhibit Cytokine Storms Contribute to the Alleviation of Sepsis

Abstract: Sepsis is a disease characterized by multiple organ failure caused by immune hyperactivation and cytokine storms. Studies have shown that the incidence of sepsis in melanoma patients is substantially lower compared to the general population. It is also observed that experimental tumor‐bearing animals have high survival rates after sepsis induction, suggesting that tumors may suppress sepsis‐associated immune overactivation, thereby alleviating sepsis. Based on the above‐described findings, this work assesses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…In order to examine the cellular membrane protein orientation on NVs and LNVs, immunolabeling with antibodies probed against their extracellular domain was designed (Figure S13A). CD44 and CD45 are glycoproteins with high expression on the cellular surface . Herein, PE-labeled anti-CD44 and PerCP-Cy5.5-labeled anti-CD45 antibodies were applied to bind the corresponding extracellular domain through surface staining and examined by flow cytometry (FCM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to examine the cellular membrane protein orientation on NVs and LNVs, immunolabeling with antibodies probed against their extracellular domain was designed (Figure S13A). CD44 and CD45 are glycoproteins with high expression on the cellular surface . Herein, PE-labeled anti-CD44 and PerCP-Cy5.5-labeled anti-CD45 antibodies were applied to bind the corresponding extracellular domain through surface staining and examined by flow cytometry (FCM).…”
Section: Resultsmentioning
confidence: 99%
“…32 CD44 and CD45 are glycoproteins with high expression on the cellular surface. 36 Herein, PE-labeled anti-CD44 and PerCP-Cy5.5labeled anti-CD45 antibodies were applied to bind the corresponding extracellular domain through surface staining and examined by flow cytometry (FCM). Both CD44 and CD45 were detected, showing a positive ratio of ∼70%, which suggested the presence of these membrane proteins on the surface of NVs and LNVs.…”
Section: Resultsmentioning
confidence: 99%
“…Sepsis is a life-threatening disease caused by microbial infection-induced immune hyperactivation and cytokine storms. Inspired by the fact that melanoma patients have a low incidence of sepsis and experimental tumor-bearing animals have high survival rates after sepsis induction, Li and co-workers found that induced exosomes (iExo) secreted from LPS-treated cancer cells could alleviate sepsis effectively compared to normal exosomes (nExo) . Then, the antisepsis mechanism of iExo was investigated.…”
Section: Nanosystems For Suppressing Excessive Immune Responses Again...mentioning
confidence: 99%
“…Inspired by the fact that melanoma patients have a low incidence of sepsis and experimental tumor-bearing animals have high survival rates after sepsis induction, Li and co-workers found that induced exosomes (iExo) secreted from LPS-treated cancer cells could alleviate sepsis effectively compared to normal exosomes (nExo). 66 Then, the antisepsis mechanism of iExo was investigated. iExo could inhibit the expression of TLR4, myeloid differentiation primary-response protein 88 (MyD88), and NF-κB, impede LPS-induced macrophage M1 polarization and promote M2 polarization, and downregulate the levels of adhesion molecules (such as ICAM-1 and chemokine MCP-1) in endothelial cells.…”
Section: Nanosystems For Suppressing Excessive Immune Responses Again...mentioning
confidence: 99%
“…Sepsis is, thus, a situation where there is a pronounced stimulation of innate immunity along with the inhibition of the conventional T-cell-originated immune response and with an increase in regulatory T cells (Tregs). This, then, provokes the onset of a sepsis-correlated immunosuppression [ 39 , 40 , 41 ] and leads to a disturbance of the immune response and possible subsequent organ damage [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%